Tempeh Waste as a Natural, Economical Carbon and Nutrient Source: ED-XRF and NCS Study - SITI KHODIJAH CHAERUN (Bogor Agricultural University, Indonesia, 2009)
The purpose of this study was to determine the elemental composition of three types of waste from tempeh production. They are soybean hull “tempeh waste” after dehulling soybeans, tempeh wastewater after soaking dehulled soybeans in water for 24 h, and tempeh wastewater after boiling dehulled soybeans in water for 30 min. By using ED-XRF analyzer, it was revealed that tempeh waste contained Mg, Si, P, S, K, Ca, Mn, Fe, and Zn. The highest elemental content was K, followed by Ca, P, and Mg. NCS analysis showed that tempeh waste was composed of C, N, and S with C/N ratio of 11.20. The present study provides evidence that both tempeh waste and wastewater are rich in carbon and nutrient contents, thus their potential for both inorganic and organic nutrient and carbon sources for microbial growth in bioremediation or as natural NPK fertilizers is promising. Key words: bioremediation, NPK fertilizer, tempeh wastewater, tempeh waste